Metal organic framework nanofiber for separating methane and nitrogen as well as preparation method and application of metal organic framework nanofiber

Zr-FUM-FA@PAN fibers were prepared by electrospinning and in-situ growth technology, which solved the problem of powder materials in the separation of methane and nitrogen, and achieved efficient gas separation and recovery while maintaining the performance of MOF materials.

CN120984248APending Publication Date: 2025-11-21GUANGXI UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511202614.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-27
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

In existing technologies, the separation of methane and nitrogen is difficult to achieve efficiently. Powder materials cause problems such as pressure drop, pipeline blockage, and low separation efficiency, and polymer fiber-coated MOF materials reduce performance.

Method used

Using electrospinning and in-situ growth techniques, Zr-FUM-FA is loaded onto PAN nanofibers to form Zr-FUM-FA@PAN fibers. The MOF powder is converted into nanofibers through electrospinning, and in-situ growth ensures that the MOF is exposed on the fiber surface.

Benefits of technology

It achieves efficient separation of methane and nitrogen, and the fiber has good adsorption and recyclability, which improves the separation efficiency, overcomes the defects of powder materials, and maintains the original performance of MOF materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120984248A_ABST
    Figure CN120984248A_ABST
Patent Text Reader

Abstract

The invention provides a metal organic framework nanofiber for methane and nitrogen separation as well as a preparation method and application of the metal organic framework nanofiber. The method comprises the following steps: obtaining a fumaric acid-loaded PAN nanofiber through an electrostatic spinning technology, then soaking the fiber in a spinning solution, and loading Zr-FUM-FA on the PAN nanofiber through a hydrothermal reaction to obtain a fiber with good CH4 adsorption performance; the nanofiber has good adsorption and separation performance, high-purity methane can be separated from mixed gas of CH4 and N2, meanwhile, the nanofiber has good recoverability and is convenient to recycle, and the problems that powder materials are difficult to recover, the pressure drop is high and the like are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of adsorption and separation materials, specifically to a metal-organic framework nanofiber for the separation of methane and nitrogen. The invention also relates to the preparation method and application of the metal-organic framework nanofiber. Background Technology

[0002] Natural gas is a gaseous fossil fuel. Compared to fossil fuels such as oil and coal, natural gas has advantages such as high calorific value, high conversion rate, lower cost, and cleaner composition, making it a promising candidate for becoming a fossil fuel with significantly increasing demand. Therefore, the efficient recovery of CH4 from unconventional natural gas is crucial for maximizing the utilization of CH4 resources and mitigating global temperature rise. Among the many impurities in natural gas, N2 and CH4 share similar physicochemical properties, making the removal of N2 to produce high-quality fuel gas extremely important.

[0003] Adsorption has garnered significant attention as an energy-efficient alternative separation technique. However, the adsorption separation of CH4 and N2 molecules is particularly challenging due to their similar kinetic diameters and polarizabilities. Metal-organic frameworks (MOFs) are relatively new hybrid porous materials that combine organic ligands with inorganic clusters to form unique pore structures. The ability to coordinate the connection of pre-designed organic molecular building blocks, coupled with nanoscale porosity and adaptability designed to capture specific target species, offers immense potential for MOF applications across various fields. However, in practical applications, using powdered MOFs leads to challenges such as pressure drop, pipe blockage, dust, low separation efficiency, mass loss, and difficulties in handling and transportation. To overcome these issues, MOF powders need to be shaped to the sizes and forms required for practical applications.

[0004] Electrospinning is a simple technique for preparing nanofibers using various materials (such as ceramics and polymers) under voltage. A common method involves dissolving or dispersing powdered materials in a polymer melt or solution and then stretching them into nanofibers using electrostatic forces. However, this method results in MOF crystals being encapsulated within the fiber and not exposed to the environment. In contrast, fibers obtained through in-situ growth ensure that the vast majority of MOFs are exposed on the fiber surface, thus preserving the original properties of the MOF material as much as possible. Summary of the Invention

[0005] To address the aforementioned problems, the first objective of this invention is to provide a metal-organic framework nanofiber for the separation of methane and nitrogen. This fiber exhibits excellent adsorption and separation properties, enabling the separation of high-purity methane from a mixture of methane and nitrogen. It also overcomes the problems of difficult recovery of powder materials and high pressure drop, while avoiding the performance degradation associated with extensive coating of MOF materials with polymer fibers.

[0006] The second objective of this invention is to provide a method for preparing metal-organic framework nanofibers for the separation of methane and nitrogen, by structuring MOF powder through electrospinning and in-situ growth techniques.

[0007] A third objective of this invention is to provide a method for separating methane and nitrogen, with high efficiency in separating CH4 / N2 mixed gases.

[0008] Therefore, the first technical solution provided by this invention is as follows:

[0009] A method for preparing metal-organic framework nanofibers for the separation of methane and nitrogen includes the following steps:

[0010] 1) Add fumaric acid and polyacrylonitrile (PAN) to the solvent and stir to dissolve to obtain a spinning solution;

[0011] 2) The spinning solution obtained in step 1) is electrospun and dried to obtain a fiber membrane loaded with fumaric acid, which is denoted as fumaric acid fiber (FUM / PAN fiber).

[0012] 3) Zirconium chloride and fumaric acid were dispersed in a mixed solution by ultrasonication to obtain a precursor solution;

[0013] 4) The metal-organic framework nanofibers Zr-FUM-FA@PAN are obtained by soaking fumaric acid cellulose in the precursor solution obtained in step 3) and then reacting them with hydrothermal reaction.

[0014] Furthermore, in step 1), the mass ratio of fumaric acid to polyacrylonitrile is 0.1 to 0.5:1;

[0015] Furthermore, the ratio of fumaric acid, PAN, and DMF used is 0.1–0.5 g: 1 g: 10 ml.

[0016] Furthermore, the stirring temperature in step 1) is 65°C, and the stirring time is 4 hours.

[0017] Furthermore, in step 2), the distance between the electrospinning needle and the roller during electrospinning is 10-17 cm; the electrospinning feed speed is 1.5-0.5 mL / h; and the electrospinning voltage is 15-17 kV.

[0018] Furthermore, in step 2), the distance between the electrospinning needle and the roller during electrospinning is 17cm; the electrospinning feed speed is 0.5mL / h; and the electrospinning voltage is 16kV.

[0019] Furthermore, the electrospinning environment is characterized by a temperature of 30°C, a humidity of 65%, a receiving roller speed of 280 rpm, a needle type of 23G, and an inner diameter of 0.34 mm.

[0020] Furthermore, in step 3), the molar ratio of zirconium chloride to fumaric acid is 1:1.

[0021] Furthermore, the solvent in step 1) is DMF, and the mixed solution in step 3) is composed of formic acid and water in a volume ratio of 1:2.

[0022] Furthermore, the ratio of zirconium chloride, formic acid, and water is 0.045–0.9 g: 1 mL: 2 mL.

[0023] Furthermore, in step 4), the reaction temperature is 100℃ and the reaction time is 24h.

[0024] Furthermore, the FUM / PAN fiber size is 30cm × (5~20)cm.

[0025] Adsorption and separation performance test of Zr-FUM-FA@PAN fiber:

[0026] The fiber membrane was subjected to single-component adsorption tests for CH4 and N2 using a physical adsorption instrument, and the specific surface area, pore size, and pore volume were calculated. The fiber membrane was loaded into an adsorption column and installed on a self-made permeation device. After the CH4 / N2 mixed gas flow rate stabilized, the mixed gas was passed through the adsorption column, and the exhaust gas composition was monitored in real time using gas chromatography.

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] 1. This invention uses electrospinning and in-situ growth technology to load Zr-FUM-FA onto PAN nanofibers, which not only have the adsorption properties of the powder material itself, but also have good recyclability and are convenient for recycling.

[0029] 2. The Zr-FUM-FA material used in this invention has suspended -OH groups, which effectively divides the material into two symmetrical shared-wall triangular pores. This facilitates the efficient adsorption of CH4 with high polarizability and demonstrates a high efficiency in separating CH4 / N2 mixed gases.

[0030] 3. The Zr-FUM-FA@PAN fiber prepared by this invention has a specific surface area as high as 334.06 m². 2 / g; the IAST selectivity of CH4 / N2 at 273K and 1 bar was 13.91; in the dynamic breakthrough experiment of CH4 / N2 mixed gas, the dynamic adsorption capacity of CH4 was 18.52 cm⁻¹. 3 / g, with a separation coefficient of 10.48 for N2. Attached Figure Description

[0031] Figure 1 SEM image of Zr-FUM-FA@PAN fibers prepared in Example 8;

[0032] Figure 2 Infrared spectrum of Zr-FUM-FA@PAN fiber prepared in Example 8;

[0033] Figure 3 Nitrogen adsorption-desorption curves at 77K for Zr-FUM-FA powder and Zr-FUM-FA@PAN fibers prepared in Example 8;

[0034] Figure 4 methane adsorption-desorption curves at 273 K for Zr-FUM-FA powder and Zr-FUM-FA@PAN fibers prepared in Example 8;

[0035] Figure 5 Nitrogen adsorption-desorption curves at 273 K for Zr-FUM-FA powder and Zr-FUM-FA@PAN fibers prepared in Example 8;

[0036] Figure 6 273 KN2 / CH4 (V / V = 50:50) IAST selectivity for Zr-FUM-FA powder and Zr-FUM-FA@PAN fibers prepared in Example 8;

[0037] Figure 7 The Zr-FUM-FA@PAN fiber prepared in Example 8 is used in the dynamic N2 / CH4 (V / V = 50:50) penetration curve. Detailed Implementation

[0038] The preferred embodiments of the present invention will now be described in detail so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby providing a clearer and more explicit definition of the scope of protection of the present invention.

[0039] Example 1

[0040] This embodiment provides a metal-organic framework nanofiber for the separation of methane and nitrogen, which is prepared sequentially through the following steps:

[0041] (1) Take 0.2g of fumaric acid and 1g of polyacrylonitrile (PAN) and add them to 10ml of DMF. Stir at 65℃ for 4h to obtain the spinning solution.

[0042] (2) Electrospinning was performed on the solution obtained in step (1), with a receiving distance of 17 cm, an injection speed of 0.6 mL / h, and a voltage of 16 kV, to obtain FUM / PAN fibers, which were denoted as FUM / PAN(0.2) fibers.

[0043] (3) Place the FUM / PAN fiber obtained in step (2) in a forced-air drying oven at 60°C and dry for 12 hours.

[0044] (4) Add 0.7g zirconium chloride and 0.35g fumaric acid to 16ml formic acid and 32mL water, sonicate at room temperature for 10min, and then transfer the suspension into the reaction vessel.

[0045] (5) Cut a 30cm×5cm piece of FUM / PAN(0.2) fiber, immerse it completely in the solution obtained in step (4), and then heat it at 100°C for 24 hours.

[0046] (6) After the reaction was completed, the fiber was washed twice with water and ethanol and dried at 60°C to obtain Zr-FUM-FA@PAN(S1) fiber.

[0047] Approximately 0.07 g of Zr-FUM-FA@PAN(S1) fiber sample was placed in a sample tube and activated under vacuum at 120℃ for 12 h. After activation, the sample tube was mounted on a BELSORP-maxⅡ physical adsorption instrument for nitrogen adsorption tests at 77 K or methane adsorption tests at 273 K. Based on the 77 K nitrogen adsorption curve, the specific surface area of ​​Zr-FUM-FA@PAN(S1) fiber was calculated using the BET and NLDFT methods. The result showed that the specific surface area of ​​Zr-FUM-FA@PAN(S1) fiber was 115.8 m². 2 / g, with an adsorption capacity of 7.62cm³ for CH4 at 273K and 1 bar. 3 / g.

[0048] Example 2

[0049] This embodiment provides a metal-organic framework nanofiber for the separation of methane and nitrogen, which is prepared sequentially through the following steps:

[0050] (1) Take 0.2g of fumaric acid and 1g of PAN and add them to 10ml of DMF. Stir at 65℃ for 4h to obtain the spinning solution.

[0051] (2) Electrospinning was performed on the solution obtained in step (1), with a receiving distance of 17 cm, an injection speed of 0.6 mL / h, and a voltage of 16 kV, to obtain FUM / PAN fibers, which were denoted as FUM / PAN(0.2) fibers.

[0052] (3) Place the FUM / PAN fiber obtained in step (2) in a forced-air drying oven at 60°C and dry for 12 hours.

[0053] (4) Add 0.7g zirconium chloride and 0.35g fumaric acid to 16ml formic acid and 32mL water, sonicate at room temperature for 10min, and then transfer the suspension into the reaction vessel.

[0054] (5) Cut a 30cm×10cm piece of FUM / PAN(0.2) fiber, immerse it completely in the solution obtained in step (4), and then heat it at 100°C for 24 hours.

[0055] (6) After the reaction was completed, the fiber was washed twice with water and ethanol and dried at 60°C to obtain Zr-FUM-FA@PAN(S2) fiber.

[0056] Approximately 0.07 g of Zr-FUM-FA@PAN(S2) fiber sample was placed in a sample tube and activated under vacuum at 120℃ for 12 h. After activation, the sample tube was mounted on a BELSORP-maxⅡ physical adsorption instrument for nitrogen adsorption tests at 77 K or methane adsorption tests at 273 K. Based on the 77 K nitrogen adsorption curve, the specific surface area of ​​Zr-FUM-FA@PAN(S2) fiber was calculated using the BET and NLDFT methods. The result showed that the specific surface area of ​​Zr-FUM-FA@PAN(S2) fiber was 159.74 m². 2 / g, with an adsorption capacity of 10.38 cm⁻¹ for CH₄ at 273 K and 1 bar. 3 / g.

[0057] Example 3

[0058] This embodiment provides a metal-organic framework nanofiber for the separation of methane and nitrogen, which is prepared sequentially through the following steps:

[0059] (1) Take 0.2g of fumaric acid and 1g of PAN and add them to 10ml of DMF. Stir at 65℃ for 4h to obtain the spinning solution.

[0060] (2) Electrospinning was performed on the solution obtained in step (1), with a receiving distance of 17 cm, an injection speed of 0.6 mL / h, and a voltage of 16 kV, to obtain FUM / PAN fibers, which were denoted as FUM / PAN(0.2) fibers.

[0061] (3) Place the FUM / PAN fiber obtained in step (2) in a forced-air drying oven at 60°C and dry for 12 hours.

[0062] (4) Add 0.7g zirconium chloride and 0.35g fumaric acid to 16ml formic acid and 32mL water, sonicate at room temperature for 10min, and then transfer the suspension into the reaction vessel.

[0063] (5) Cut a 30cm×15cm piece of FUM / PAN(0.2) fiber, immerse it completely in the solution obtained in step (4), and then heat it at 100°C for 24 hours.

[0064] (6) After the reaction was completed, the fiber was washed twice with water and ethanol and dried at 60°C to obtain Zr-FUM-FA@PAN(S3) fiber.

[0065] Approximately 0.07 g of Zr-FUM-FA@PAN(S3) fiber sample was placed in a sample tube and activated under vacuum at 120℃ for 12 h. After activation, the sample tube was mounted on a BELSORP-maxⅡ physical adsorption instrument for nitrogen adsorption tests at 77 K or methane adsorption tests at 273 K. Based on the 77 K nitrogen adsorption curve, the specific surface area of ​​Zr-FUM-FA@PAN(S3) fiber was calculated using the BET and NLDFT methods. The result showed that the specific surface area of ​​Zr-FUM-FA@PAN(S3) fiber was 199.85 m². 2 / g, with an adsorption capacity of 13.25cm for CH4 at 273K and 1 bar. 3 / g.

[0066] Example 4

[0067] This embodiment provides a metal-organic framework nanofiber for the separation of methane and nitrogen, which is prepared sequentially through the following steps:

[0068] (1) Take 0.2g of fumaric acid and 1g of PAN and add them to 10ml of DMF. Stir at 65℃ for 4h to obtain the spinning solution.

[0069] (2) Electrospinning was performed on the solution obtained in step (1), with a receiving distance of 17 cm, an injection speed of 0.6 mL / h, and a voltage of 16 kV, to obtain FUM / PAN fibers, which were denoted as FUM / PAN(0.2) fibers.

[0070] (3) Place the FUM / PAN fiber obtained in step (2) in a forced-air drying oven at 60°C and dry for 12 hours.

[0071] (4) Add 0.7g zirconium chloride and 0.35g fumaric acid to 16ml formic acid and 32mL water, sonicate at room temperature for 10min, and then transfer the suspension into the reaction vessel.

[0072] (5) Cut a 30cm×20cm piece of FUM / PAN(0.2) fiber, immerse it completely in the solution obtained in step (4), and then heat it at 100°C for 24 hours.

[0073] (6) After the reaction was completed, the fiber was washed twice with water and ethanol and dried at 60°C to obtain Zr-FUM-FA@PAN(S4) fiber.

[0074] Approximately 0.07 g of Zr-FUM-FA@PAN(S4) fiber sample was placed in a sample tube and activated under vacuum at 120℃ for 12 h. After activation, the sample tube was mounted on a BELSORP-maxⅡ physical adsorption instrument for nitrogen adsorption tests at 77 K or methane adsorption tests at 273 K. Based on the 77 K nitrogen adsorption curve, the specific surface area of ​​Zr-FUM-FA@PAN(S4) fiber was calculated using the BET and NLDFT methods. The result showed that the specific surface area of ​​Zr-FUM-FA@PAN(S4) fiber was 200.13 m². 2 / g, with an adsorption capacity of 13.19 cm⁻¹ for CH₄ at 273 K and 1 bar. 3 / g.

[0075] Example 5

[0076] This embodiment provides a metal-organic framework nanofiber for the separation of methane and nitrogen, which is prepared sequentially through the following steps:

[0077] (1) Take 0.3g of fumaric acid and 1g of PAN and add them to 10ml of DMF. Stir at 65℃ for 4h to obtain the spinning solution.

[0078] (2) Electrospinning was performed on the solution obtained in step (1), with a receiving distance of 17 cm, an injection speed of 0.6 mL / h, and a voltage of 16 kV, to obtain FUM / PAN fibers, which are denoted as FUM / PAN(0.3) fibers.

[0079] (3) Place the FUM / PAN fiber obtained in step (2) in a forced-air drying oven at 60°C and dry for 12 hours.

[0080] (4) Add 0.7g zirconium chloride and 0.35g fumaric acid to 16ml formic acid and 32mL water, sonicate at room temperature for 10min, and then transfer the suspension into the reaction vessel.

[0081] (5) Cut a 30cm×15cm piece of FUM / PAN(0.3) fiber, immerse it completely in the solution obtained in step (4), and then heat it at 100°C for 24 hours.

[0082] (6) After the reaction was completed, the fiber was washed twice with water and ethanol and dried at 60°C to obtain Zr-FUM-FA@PAN(L3) fiber.

[0083] Approximately 0.07 g of Zr-FUM-FA@PAN(L3) fiber sample was placed in a sample tube and activated under vacuum at 120℃ for 12 h. After activation, the sample tube was mounted on a BELSORP-maxⅡ physical adsorption instrument for nitrogen adsorption tests at 77 K or methane adsorption tests at 273 K. Based on the 77 K nitrogen adsorption curve, the specific surface area of ​​the Zr-FUM-FA@PAN(L3) fiber was calculated using the BET and NLDFT methods. The result showed that the specific surface area of ​​the Zr-FUM-FA@PAN(L3) fiber was 233.02 m². 2 / g, with an adsorption capacity of 15.31cm for CH4 at 273K and 1 bar. 3 / g.

[0084] Example 6

[0085] This embodiment provides a metal-organic framework nanofiber for the separation of methane and nitrogen, which is prepared sequentially through the following steps:

[0086] (1) Take 0.5g of fumaric acid and 1g of PAN and add them to 10ml of DMF. Stir at 65℃ for 4h to obtain the spinning solution.

[0087] (2) Electrospinning was performed on the solution obtained in step (1), with a receiving distance of 17 cm, an injection speed of 0.6 mL / h, and a voltage of 16 kV to obtain FUM / PAN fibers, which were denoted as FUM / PAN(0.5) fibers.

[0088] (3) Place the FUM / PAN fiber obtained in step (2) in a forced-air drying oven at 60°C and dry for 12 hours.

[0089] (4) Add 0.7g zirconium chloride and 0.35g fumaric acid to 16ml formic acid and 32mL water, sonicate at room temperature for 10min, and then transfer the suspension into the reaction vessel.

[0090] (5) Cut a 30cm×15cm piece of FUM / PAN(0.5) fiber, immerse it completely in the solution obtained in step (4), and then heat it at 100°C for 24 hours.

[0091] (6) After the reaction was completed, the fiber was washed twice with water and ethanol and dried at 60°C to obtain Zr-FUM-FA@PAN(L5) fiber.

[0092] Approximately 0.07 g of Zr-FUM-FA@PAN(L5) sample fiber was placed in a sample tube and activated under vacuum at 120 °C for 12 h. After activation, the sample tube was mounted on a BELSORP-maxⅡ physical adsorption instrument for nitrogen adsorption tests at 77 K or methane adsorption tests at 273 K. Based on the 77 K nitrogen adsorption curve, the specific surface area of ​​the Zr-FUM-FA@PAN(L5) fiber was calculated using the BET and NLDFT methods. The result showed that the specific surface area of ​​the Zr-FUM-FA@PAN(L5) fiber was 235.65 m². 2 / g, with an adsorption capacity of 15.22 cm⁻¹ for CH₄ at 273 K and 1 bar. 3 / g.

[0093] Example 7

[0094] This embodiment provides a metal-organic framework nanofiber for the separation of methane and nitrogen, which is prepared sequentially through the following steps:

[0095] (1) Take 0.5g of fumaric acid and 1g of PAN and add them to 10ml of DMF. Stir at 65℃ for 4h to obtain the spinning solution.

[0096] (2) Electrospinning was performed on the solution obtained in step (1), with a receiving distance of 17 cm, an injection speed of 0.6 mL / h, and a voltage of 16 kV to obtain FUM / PAN fibers, which were denoted as FUM / PAN(0.5) fibers.

[0097] (3) Place the FUM / PAN fiber obtained in step (2) in a forced-air drying oven at 60°C and dry for 12 hours.

[0098] (4) Add 1.05g zirconium chloride and 0.525g fumaric acid to 16ml formic acid and 32mL water, sonicate at room temperature for 10min, and then transfer the suspension into the reaction vessel.

[0099] (5) Cut a 30cm×15cm piece of FUM / PAN(0.5) fiber, immerse it completely in the solution obtained in step (4), and then heat it at 100°C for 24 hours.

[0100] (6) After the reaction is complete, the fiber is washed twice with water and ethanol and dried at 60°C to obtain Zr-FUM-FA@PAN(C1.5) fiber.

[0101] Approximately 0.07 g of Zr-FUM-FA@PAN(C1.5) fiber sample was placed in a sample tube and activated under vacuum at 120℃ for 12 h. After activation, the sample tube was mounted on a BELSORP-maxⅡ physical adsorption instrument for nitrogen adsorption tests at 77 K or methane adsorption tests at 273 K. Based on the 77 K nitrogen adsorption curve, the specific surface area of ​​Zr-FUM-FA@PAN(C1.5) fiber was calculated using the BET and NLDFT methods. The result showed that the specific surface area of ​​Zr-FUM-FA@PAN(C1.5) fiber was 274.99 m². 2 / g, with an adsorption capacity of 17.34 cm⁻¹ for CH₄ at 273 K and 1 bar. 3 / g.

[0102] Example 8

[0103] This embodiment provides a metal-organic framework nanofiber for the separation of methane and nitrogen, which is prepared sequentially through the following steps:

[0104] (1) Take 0.5g of fumaric acid and 1g of PAN and add them to 10ml of DMF. Stir at 65℃ for 4h to obtain the spinning solution.

[0105] (2) Electrospinning was performed on the solution obtained in step (1), with a receiving distance of 17 cm, an injection speed of 0.6 mL / h, and a voltage of 16 kV to obtain FUM / PAN fibers, which were denoted as FUM / PAN(0.5) fibers.

[0106] (3) Place the FUM / PAN fiber obtained in step (2) in a forced-air drying oven at 60°C and dry for 12 hours.

[0107] (4) Add 1.4g zirconium chloride and 0.7g fumaric acid to 16ml formic acid and 32mL water, sonicate at room temperature for 10min, and then transfer the suspension into the reaction vessel.

[0108] (5) Cut a 30cm×15cm piece of FUM / PAN(0.5) fiber, immerse it completely in the solution obtained in step (4), and then heat it at 100°C for 24 hours.

[0109] (6) After the reaction was completed, the fiber was washed twice with water and ethanol and dried at 60°C to obtain Zr-FUM-FA@PAN(C2) fiber.

[0110] SEM image of Zr-FUM-FA@PAN(C2) fiber prepared in Example 8 is shown in the figure. Figure 1 ,pass Figure 1It can be seen that the fiber surface is rough due to being covered by a large number of particles, and the fiber diameter is approximately 600–700 nm. See the infrared spectrum of Zr-FUM-FA@PAN(C2) fiber for reference. Figure 2 As can be seen from 2, at 2241cm -1 There is a characteristic absorption peak at 1675 cm⁻¹ belonging to the stretching vibration of the C≡N group. Additionally, there is a peak at 1675 cm⁻¹. -1 1233cm -1 and 1277cm -1 The peak at 400 cm⁻¹ shows a characteristic peak belonging to the C=O group of fumaric acid, indicating that fumaric acid can be well loaded onto PAN fibers. Zr-FUM-FA@PAN(C2) fibers grown in situ exhibit a characteristic peak at 400 cm⁻¹. -1 Up to 1800cm -1 They exhibit highly similar characteristic absorption peaks at 2241 cm⁻¹, and at 2241 cm⁻¹... -1 There is a characteristic absorption peak at the point that belongs to the stretching vibration of the C≡N group, indicating that Zr-FUM-FA was successfully loaded onto PAN fibers.

[0111] Take about 0.07g of Zr-FUM-FA@PAN(C2) fiber sample and place it into a sample tube. Activate it under vacuum at 120℃ for 12h. After activation, install the sample tube on a BELSORP-maxⅡ physical adsorption instrument and perform nitrogen adsorption tests at 77K or methane and nitrogen adsorption tests at 273K. Calculate the specific surface area of ​​the fiber using BET and NLDFT methods based on the 77K nitrogen adsorption curve.

[0112] Comparative Example 1

[0113] Comparative Example 1 provides a Zr-FUM-FA powder, which is prepared by the following method:

[0114] (1) Add 1.4g zirconium chloride and 0.7g fumaric acid to 16ml formic acid and 32mL water, and sonicate at room temperature for 10min to obtain a well dispersed suspension.

[0115] (2) Transfer the suspension obtained in step (1) into the reaction vessel and then heat it at 100°C for 24 hours.

[0116] (3) After the reaction vessel is cooled, the product is centrifuged and washed twice with water and ethanol, and dried at 60°C to obtain white Zr-FUM-FA powder.

[0117] Take about 0.1g of Zr-FUM-FA powder sample and place it into a sample tube. Activate it under vacuum at 120℃ for 12h. After activation, install the sample tube on a BELSORP-maxⅡ physical adsorption instrument and perform nitrogen adsorption tests at 77K or methane and nitrogen adsorption tests at 273K. Calculate the specific surface area of ​​the powder using the BET and NLDFT methods based on the 77K nitrogen adsorption curve.

[0118] The adsorption capacity for N2 and CH4 at 273 K and 1 bar was 8.55 cm⁻¹. 3 / g and 34.68cm 3 The IAST selectivity of N2 / CH4 (V / V = 50:50) was 13.77.

[0119] The 77K nitrogen adsorption-desorption curves of Zr-FUM-FA powder prepared in Comparative Example 1 and Zr-FUM-FA@PAN(C2) fiber prepared in Example 8 are shown in Figure 3. Figure 3 The adsorption curve of Zr-FUM-FA exhibits a type I curve, indicating the presence of a microporous structure. The adsorption curve of Zr-FUM-FA@PAN(C2) fiber is similar to that of Zr-FUM-FA under low pressure, indicating that both have similar microporous structures. The adsorption capacity of Zr-FUM-FA@PAN(C2) fiber increases rapidly under high pressure, exhibiting a type II curve and a relatively obvious hysteresis loop, indicating the presence of a mesoporous structure. Calculations show that the specific surface area of ​​Zr-FUM-FA is 631.37 m² / g, and the specific surface area of ​​Zr-FUM-FA@PAN(C2) fiber is 334.06 m² / g, approximately 52.91% of the powder's surface area.

[0120] Methane adsorption-desorption curves at 273 K for Zr-FUM-FA powder prepared in Comparative Example 1 and Zr-FUM-FA@PAN(C2) fibers prepared in Example 8. Figure 4 ,pass Figure 4 It can be seen that at 273 K and 1 bar, the adsorption capacity of Zr-FUM-FA for methane is 34.68 cm⁻¹. 3 / g, while the adsorption capacity of the Zr-FUM-FA@PAN(C2) fiber described in Example 8 for methane is 21.06 cm³. 3 / g, approximately 60.73% of the powder.

[0121] The nitrogen adsorption-desorption curves at 273 K for the Zr-FUM-FA powder prepared in Comparative Example 1 and the Zr-FUM-FA@PAN(C2) fiber prepared in Example 8 are shown in the figure. Figure 5 ,pass Figure 5 It can be seen that at 273 K and 1 bar, the adsorption capacity of Zr-FUM-FA for nitrogen is 8.55 cm⁻¹.3 / g, while the nitrogen adsorption capacity of the Zr-FUM-FA@PAN(C2) fiber described in Example 8 is 4.5cm³. 3 / g, approximately 52.63% of the powder.

[0122] The 273K methane and nitrogen IAST selectivity of Zr-FUM-FA powder prepared in Comparative Example 1 and Zr-FUM-FA@PAN(C2) fiber prepared in Example 8 can be found in the reference. Figure 6 ,pass Figure 6 It can be seen that at 273K and 1 bar, the selectivity of Zr-FUM-FA for N2 / CH4 (V / V = 50:50) is 13.77, and the selectivity of Zr-FUM-FA@PAN(C2) fiber for N2 / CH4 (V / V = 50:50) in Example 8 is 10.91, indicating that Zr-FUM-FA@PAN(C2) fiber has high separation potential for mixed gases of nitrogen and methane.

[0123] Application Example 1

[0124] This embodiment provides a method for separating methane and nitrogen using metal-organic framework nanofibers, which includes the following steps in sequence:

[0125] (1) 2.0g of Zr-FUM-FA@PAN(C2) fiber prepared in Example 8 was loaded into an adsorption column and installed on a self-made permeation device;

[0126] (2) The N2 / CH4 (v / v = 50:50) mixture is introduced into the empty pipe of the permeation device, and the flow rate of the mixture is controlled to be 1 sccm using a mass flow meter and a soap film flow meter.

[0127] (3) After the gas flow rate of the mixed gas in step (2) stabilizes, switch the adsorption column valve to allow the mixed gas to pass through the adsorption column in step (1);

[0128] (4) Turn on the gas chromatograph and pass the tail gas described in step (3) into the gas chromatograph for real-time detection;

[0129] (5) After the sample dynamic adsorption data is saturated, the adsorption column on the penetration device is heated at 100°C with a heating belt, and the pipeline is purged with helium at a rate of 5 sccm.

[0130] (6) Turn on the gas chromatograph and pass the tail gas described in step (5) into the gas chromatograph for real-time detection;

[0131] Based on dynamic gas chromatography data, N2 began eluting through the adsorption bed at a concentration of 5 min / g, while CH4 only began eluting at a concentration of 16 min / g. The dynamic adsorption capacity of CH4 was 18.52 cm⁻¹. 3 / g, with a separation coefficient of 10.48 for N2.

[0132] The Zr-FUM-FA@PAN(C2) fiber prepared in Example 8 was applied to the dynamic CH4 / N2 penetration curve (see attached graph). Figure 7 ,pass Figure 7 It can be seen that N2 begins to elute through the adsorption bed at 5 min / g, while CH4 only begins to elute at 16 min / g. Calculations show that the dynamic adsorption capacity of CH4 is 18.52 cm⁻¹. 3 / g, with a separation coefficient of 10.48 for N2. In subsequent desorption experiments, nitrogen was completely desorbed in less than three minutes, while the desorption time for methane was 55 minutes, thus enabling the collection of high-purity methane through desorption.

Claims

1. A metal-organic framework nanofiber for the separation of methane and nitrogen, characterized in that, The steps are as follows: 1) Add fumaric acid and polyacrylonitrile to the solvent and stir to dissolve to obtain a spinning solution; 2) The spinning solution obtained in step 1) is electrospun and dried to obtain a fiber membrane loaded with fumaric acid, which is denoted as fumaric acid fiber. 3) Zirconium chloride and fumaric acid were dispersed in a mixed solution by ultrasonication to obtain a precursor solution; 4) The fumaric acid fiber described in step 2) is soaked in the precursor solution obtained in step 3) and then subjected to hydrothermal reaction to obtain metal-organic framework nanofibers Zr-FUM-FA@PAN.

2. The method for preparing the nanofiber membrane according to claim 1, characterized in that, In step 1), the mass ratio of fumaric acid to polyacrylonitrile is 0.1 to 0.5:

1.

3. The method for preparing the nanofiber membrane according to claim 1, characterized in that, The stirring temperature in step 1) is 65℃, and the stirring time is 4 hours.

4. The method for preparing the nanofiber membrane according to claim 1, characterized in that, In step 2), the distance between the electrospinning needle and the roller during electrospinning is 10-17 cm; the electrospinning feed speed is 1.5-0.5 mL / h; and the electrospinning voltage is 15-17 kV.

5. The method for in-situ growth of MOF materials on fibers according to claim 1, characterized in that, In step 3), the molar ratio of zirconium chloride to fumaric acid is 1:

1.

6. The method for in-situ growth of MOF materials on fibers according to claim 1, characterized in that, The solvent in step 1) is DMF, and the mixed solution in step 3) is composed of formic acid and water in a volume ratio of 1:

2.

7. The method for in-situ growth of MOF materials on fibers according to claim 1, characterized in that, In step 4), the reaction temperature is 100℃ and the reaction time is 24h.

8. A metal-organic framework nanofiber, characterized in that, It is prepared by any one of the preparation methods described in claims 1-7.

9. A method for separating methane and nitrogen, characterized in that, Separation was performed using the metal-organic framework nanofibers described in claim 8.